STUDI FENOMENOLOGI MATA KULIAH ETIKA BISNIS DAN PROFESI (Studi Kasus di Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya Malang) - Ariesta, Emilio Feryawan; Achsin, M. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The education cannot escape from its function to produce a skill and an ability to be owned by someone. Moral is also established through education by creating noble behavior and personality. Moreover, the education at higher education is expected to deliver students with noble morality and character. To realize this expectation, any departments in each faculty, especially within University of Brawijaya Malang, are required to provide a specific course to create ethic and moral behavior among students. One such course is Business and Profession Ethic Course. Some students, however, may still commit unethical action even after given this course. The objective of this research is to understand the phenomenon of a process of teaching and learning Business and Profession Ethic Course. Informant includes five students of Department of Accounting of Class of 2009 and one counseling lecturer of Business and Profession Ethic Course. Research method is phenomenology qualitative method. Result of research indicates that four of five student informants experience behavioral change after attending the course. This positive change may be because of reflexivity duties given by the lecturer or the distinctive or more understandable material delivery. In the next semester, it is unfortunate to find that these student informants are committing academic fraud even attending this ethic course in previous semester. Many factors are triggering students to commit academic fraud. Result of research indicates that Business and Profession Ethic Course has not been able to change the behavior of students to avoid from doing something unethical. Keywords: Education, Business and Profession Ethic Course, Students Phenomenology